2019
DOI: 10.31616/asj.2018.0145
|View full text |Cite
|
Sign up to set email alerts
|

En Bloc Spondylectomy for Spinal Metastases: Detailed Oncological Outcomes at a Minimum of 2 Years after Surgery

Abstract: Study Design Retrospective case series. Purpose To investigate the oncological outcomes, including distant relapse, after en bloc spondylectomy (EBS) for spinal metastases in patients with a minimum of 2-year follow-up. Overview of Literature Although EBS has been reported to be locally curative and extend survival in select patients with spinal metastases, detailed reports regarding the control of distant relapse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 20 publications
0
31
0
6
Order By: Relevance
“…Although total en bloc spondylectomy is considered an ideal choice for patients with solitary spinal metastasis, the complex surgical procedure has limited the practicality of this method. In addition, Ohashi et al showed that 72.2% of patients experienced distant dissemination after en bloc resection in the long-term follow-up (>48 months) ( 26 ), indicating that en bloc resection is unable to prevent distant relapse despite the low rate of local recurrence. Moreover, compared with debulking, en bloc surgery showed similar survival outcomes, neurological improvements, and complication rates ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although total en bloc spondylectomy is considered an ideal choice for patients with solitary spinal metastasis, the complex surgical procedure has limited the practicality of this method. In addition, Ohashi et al showed that 72.2% of patients experienced distant dissemination after en bloc resection in the long-term follow-up (>48 months) ( 26 ), indicating that en bloc resection is unable to prevent distant relapse despite the low rate of local recurrence. Moreover, compared with debulking, en bloc surgery showed similar survival outcomes, neurological improvements, and complication rates ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Favorable outcomes in this regard have been reported in the literature [ 74 - 76 ]. However, some authors recently reported that curative surgical resection (en bloc spondylectomy) did not impact the oncologic outcomes of spinal metastasis patients [ 77 ]. Therefore, a more careful and thorough decision-making process is required before performing curative resection surgery for spinal metastasis, especially when the extended role of radiosurgery is considered.…”
Section: Surgery For Metastatic Spinal Tumorsmentioning
confidence: 99%
“…Contrary to the expectations of most clinicians, the development of effective and modern systemic treatment modalities has increased the number of spinal SM and the publication of related articles, especially in Asian countries [33–36, 68, 73, 77–82, 99–102]. Although the number of candidates with an indication for spinal SM is still limited among patients with spinal metastases, we expect these to increase, especially in countries where SBRT is not widely available.…”
Section: Resultsmentioning
confidence: 96%